Ideias leguminosas: um projecto Ciência-Arte no âmbito de 2016 - Ano Internacional das Leguminosas/Ideias Leguminosas - Dias, Hugo Direito (2017)
Ideias Leguminosas (Ideas on Pulses), a project in the scope of 2016 International Year of Pulses, developed between Escola Sementes de Liberdade and STOL - Science Through Our Lives (a science communication project from University of Minho) was aimed at addressing the characteristics, properties and applications of pulses through activities that exploited the students' cognitive, emotional and social skills and allowed the school to be involved with the closest community in a science communication "service" to society. Examples of this are: the construction of the creative text "Fabacea, in the realm of improbable loves" with later theatrical staging and public performance in the form of puppet theater and illustration; the creation of the board game "Fabacea" that was present at the European Researchers Night (Braga), the Pulses Festival (Lisbon) and the exhibition "Missing images from the past? Not even in beans!" (Perder imagens do passado? Nem a feijões!”) (Braga); the presentation of a communication at the SciCom PT 2016 congress (Lisbon); the writing of lyrics; the planting of a garden and; the idealization of hands-on objects about concepts as diverse as pulse, symbiosis, bacteria, water footprint and protein content. These materials also allowed us to focus on emerging issues such as sustainability and healthy eating. With this workshop we deeply suggest the theme "Pulses" to be approached in the curricular areas of Portuguese, Mathematics and Study of the Surroundings (Estudo do Meio), using learning ware produced by and for the pupils. One of them is the "Fabaceae" board game designed with skills on mathematics and portuguese, which allows players to learn several concepts about pulses while outlining strategies to win the challenge. Other materials are origami fortune-tellers, simple visual models of the water footprint of different foods and match sets that allow the identification of different pulses. With this workshop we intend to demonstrate the potential of the project work in teaching and in Science communication, by using a holistic approach, from childhood, making the concepts contextual and meaningful. Additionally, it is our purpose to show how science teaching can be done without costly and difficult access logistics.